Management accounting as an effective tool of management of a modern enterprise - Shurpenkova, Ruslana; Sarahman, Oksana (Współczesne Problemy Zarządzania, 2021)
The article analyzes the role of managerial accounting in the enterprise management system. It is established that managerial accounting is an effective management tool because it creates competitive advantages in a market environment. The main principles of managerial accounting system construction at the enterprise are highlighted, its importance for effective functioning is substantiated. The main problems hindering the management accounting implementation and planned measures for successful implementation of this process at Ukrainian enterprises are also analyzed.